The application of regional culture in urban public space design - Li, Ya; Faridah, Sahari (Taylor & Francis Group, 2022)
With the pace of urbanization and globalization gradually accelerated. Many urban public Spaces focus on “modern”, “fashion” and “international” while ignoring the important role of traditional history and regional culture in public Spaces, which leads to serious homogeneity in both external form and cultural expression in many urban public Spaces. A good urban public space environment should make people have a sense of historical belonging and show the characteristics of the city. This paper discusses the importance of regional culture in urban construction, and tries to make those excellent regional culture continue and inherit in urban public space design by creatively extracting regional cultural elements and combining them with modern design techniques. Through case analysis, this paper expounds the specific design and expression method of urban regional culture, thus proving that regional culture has very important significance and necessity in creating personalized urban public space. Subjects: Cultural Heritage; Urban Studies; Urban Cultures; Urban Policy; Urban Research Methods; Landscape and Sustainability; Urban Landscape; Urban Design; Design; Heritage